Analisis Kesalahan Siswa SMP dalam Menyelesaikan Soal Cerita Bilangan Bulat - Rahayuningsih, Sri; Astuti, Tri Yanti Yuli (Jurnal Likhitaprajna, 2020)
This study aims to analyze the errors of junior high school students in solving integer story questions. The type of research that will be used is descriptive qualitative. 24 students of grade VII SMP were made participants. The instruments used were in the form of integer story questions and semi-structured interview sheets. The data collection procedure began by giving test questions to participants. The work of students who experience a lot of mistakes is analyzed using the Newman or NEA (Newman Error Error) procedure. Obtained three groups of students who experienced the same error in solving integer story questions in writing. One student was taken from each group to represent what is hereinafter referred to as subject 1 (S1), Subject 2 (S2), Subject 3 (S3). The results obtained indicated that in completing the whole number story problem, S1 did not understand the overall meaning, so there was some information that was missed on the purpose of the problem or question. S2 understands the problem contained in the problem, but cannot write information in mathematical form, and does not do calculations correctly. S3 could not perform mathematical calculations or procedures correctly. The researcher concluded that students who experience errors in reading problems would experience four other errors, namely errors in understanding and problem transformation, then students would also experience errors in process skills and errors in writing the final result.